Article Effects of exercise program and 3R technique to increase Muscle power and Balance of Children with Intellectual Disabilities. - Sanpet, Ariwat (Al-HIKMAH Journal, 2023)
The objectives of this research were to. 1) Compare Muscle Power of children with Intellectual Disabilities before and after using the exercise program and 3R teaching techniques. 2) Compare Balance of children with Intellectual Disabilities before and after using the exercise program and 3R teaching techniques. 3) Study the satisfaction of exercise program users and 3R teaching techniques to increase Muscle Power and Balance of children with Intellectual Disabilities. This research is a quasi experimental research. The target group of this research was children with Intellectual Disabilities aged 4-7 years 5 children. By purposive random sampling. The research tool was an Exercise Program and 3R teaching techniques for 6 activity for 6 weeks, 3 time/week, 40 minutes/time, total 18 times. The statistics used for data analysis were the mean (x) and the standard deviation (S.D) of the Muscle Power and Balance test scores. and satisfaction of Exercise Program users and 3R teaching techniques. The results revealed that. 1) The Muscle Power of children with Intellectual Disabilities after using the exercise program and the 3R teaching technique increased more than before use in all children. 2) The Balance of children with Intellectual Disabilities after using the exercise program and 3R teaching technique all students had higher Balance than before use in all children. 3) Satisfaction of exercise program users and 3R teaching techniques averaged in all aspects. The mean was at a high level ( x= 3.91, S.D. = 0.15).